Removal of Some Traces Heavy Metals from Aqueous Solutions by Water Hyacinth Leaves Powder - Hassoon, Hassanein A.; Najem, Ali M. (Iraqi Journal of Science, 2022)
The pollution of aquatic ecosystems with toxic heavy metals is representing a major environmental issue, as a result of releasing these metals to ecological ambient without treatment, leading to their persistence and non-biodegradation in the environment. Various traditional methods are utilized as an attempt to remove heavy metals from waste water but still without making any actual progress. This study hypothesizes that Eichhornia crassipes (water hyacinth) dried leaves powder is potential in removing some of these heavy metals (HM), including lead, copper, cadmium and chrome from aqueous solutions via biosorption influenced by some variable experimental factors. This aim was approached by using two different experimental conditions: (i) investigating the effect of different pH values, ranged between 4-8 with a constant (HM) concentration (1000 ppm), (ii) using variable (HM) concentrations with a range (250, 500, 750 and 1000 ppm) in which constant pH value equal to 7 was maintained. Additionally, the amount of leaves powder used throughout the study was 1g. The data obtained from this study revealed that higher removal efficiency was observed with lead (Pb) which reached to 99.9%, whereas the lowest was with chrome (Cr) which its removal was up to 80% in both experimental conditions. These results suggest that E.crassipes in its non-living form is efficient in the treatment of waste water and other industrial effluents containing trace elements.